Training in Educative Games Based on Malay Culture for Students' Indonesian Language Learning for Primary School Teachers - Lubis, Renni Ramadhani (PT. Berlian Pustaka Indonesia, 2024)
The aim of this training is to help teachers create teaching materials that not only educate, but also introduce students to the richness of their culture, thereby improving the learning experience and strengthening knowledge of Indonesian among elementary school students. This training was carried out in the form of educational game training based on Malay culture. The training was held at SD Negeri 050708 Kampung Teluk on Tuesday, 16 July 2024, which started at 08.00 - 16.00 Wib. There were 25 participants who took part in the training, the participants consisted of 2 speakers and 23 teachers from SD Negeri 050708 Kampung Teluk. The methods used in training activities are the friendly method, practice and discussion. Meanwhile, the steps for implementing training activities are: (a) preparation stage, (b) implementation stage, (c) monitoring stage. This training has been carried out well in accordance with the expectations of the service team and partner schools. After completing the training, the service team distributed questionnaires to the participants, which aimed to find out to what extent the participants understood the material about educational games based on Malay culture that had been explained by the presenters. From the overall results of the questionnaire consisting of 10 statements that were filled in by the participants, it was found that the average percentage was 963.35%, so it can be concluded that the participants were very interested and enthusiastic in taking part in this training.